Variations of bubble cavitation and temperature elevation during acculysis - Zhou, Yufeng (2017)
High-intensity focused ultrasound (HIFU) is effective in both thermal ablations and soft-tissue fragmentation. Mechanical and thermal effects depend on the operating parameters and vary with the progress of therapy. Different types of lesions could be produced with the pulse duration of 5-30 ms, much longer than histotripsy burst but shorter than the time for tissue boiling, and pulse repetition frequency (PRF) of 0.2-5 Hz. Meanwhile, bubble cavitation and temperature elevation in the focal region were measured by passive cavitation detection (PCD) and thermocouples, respectively. Temperature in the pre-focal region is always higher than those at the focal and post-focal position in all tests. Overall, it is suggested that appropriate synergy and monitoring of mechanical and thermal effects would broaden the HIFU application and enhance its efficiency as well as safety.